Mechanisms for addressing the impact of covid-19 on infrastructure projects - S. S., King; R. A., Rahman; M. A., Fauzi; A. T., Haron (IOP Publishing Ltd, 2021)
The COVID-19 pandemic has affected the overall economy and the construction industry badly. The Movement Control Order (MCO) caused the suspension of the construction sector, including infrastructure projects. Contractors are suffering losses and facing many problems caused by the pandemic, even with the on-going government financial aids. By identifying the right approaches to improve existing government policies and strategies, contractors could better manage the problems. Thus, this research aims to explore mechanisms for reducing COVID-19's negative impact on the infrastructure construction industry. To achieve that objective, this study involves collecting and analyzing interview data with industry practitioners. The significant findings from the analysis are: (1) COVID-19 affects the infrastructure construction industry by causing financial and productivity problems; and (2) mechanisms to address those problems include legal, financial, productivity, and environmental support. This paper's finding is valuable for the government in determining the right actions in assisting contractors in this critical period.